The Correlation of Knowledge and Duration of Illness Towards Self Management With Diabetes Mellitus Patients in the Pan-demic Era of COVID-19 - Wahyuni, Sri; Wibowo, Galuh Ayu (Sahabat Publikasi Kuu, 2023)
(1) Background: Diabetes mellitus (DM) is a chronic disease that, if not treated trigger various disease, and also cause the severity of COVID-19 infection. People with DM need proper knowledge and management to improve the quality of life of patients during a pandemic and the treatment process will take a lifetime. The purpose of this study is to determine the relationship between knowledge and duration of illness on diabetes mellitus self-management; (2) Methods: The study's design is a correlational study with a cross-sectional approach, with a total sample of 138 respondents who were taken by convenience sampling technique. Data was collected using the diabetes knowledge questionnaire (DKQ-24), the COVID-19 knowledge questionnaire, and the diabetes self-management questionnaire (DSMQ); (3) Results: The Chi-Square statistical test analysis revealed a p-value of 0.00 relationship between knowledge and self-management; (4) Conclusions: There is a relationship between knowledge of diabetes mellitus and COVID-19 on self-management of diabetes mellitus, and there is no relationship between duration of illness and diabetes mellitus self-management during the COVID-19 pandemic.